Polymyxin B as inhibitor of LPS contamination of Schistosoma mansoni recombinant proteins in human cytokine analysis - Pacífico Lucila G; Góes Alfredo M; Araujo Maria; Cardoso Luciana S; Oliveira Ricardo R; Oliveira Sergio C (Microbial Cell Factories, 2007)
Abstract Background Recombinant proteins expressed in Escherichia coli vectors are generally contaminated with endotoxin. In this study, we evaluated the ability of Polymyxin B to neutralize the effect of LPS present as contaminant on Schistosoma mansoni recombinant proteins produced in E. coli in inducing TNF-α and IL-10. Peripheral blood mononuclear cells from individuals chronically infected with S. mansoni were stimulated in vitro with recombinant Sm22.6, Sm14 and P24 antigens (10 μg/mL) in the presence of Polymyxin B (10 μg/mL). Results The levels of cytokines were measured using ELISA. There was greater than 90 % reduction (p < 0.05) in the levels of TNF-α and IL-10 when Polymyxin B was added to the cultures stimulated with LPS. In cultures stimulated with S. mansoni recombinant proteins in the presence of Polymyxin B, a reduction in the levels of TNF-α and IL-10 was also observed. However, the percentage of reduction was lower when compared to the cultures stimulated with LPS, probably because these proteins are able to induce the production of these cytokines by themselves. Conclusion This study showed that Polymyxin B was able to neutralize the effect of endotoxin, as contaminant in S. mansoni recombinant antigens produced in E. coli, in inducing TNF-α and IL-10 production.